Initiation of antiretroviral therapy or antiretroviral prophylaxis in pregnant women living with HIV registered in five townships of Mandalay, Myanmar: A cross sectional study - Khine Wut Yee Kyaw; Aye Aye Mon; Khaing Hnin Phyo; Nang Thu Thu Kyaw; Ajay M. V. Kumar; Than Than Lwin; Zaw Zaw Aung; Thet Ko Aung; Myo Minn Oo; Thurain Htun; Sai Soe Thu Ya; Srinath Satyanarayana; et al. (BMC, 2019)
Abstract Background A series of interventions are required to prevent mother to child transmission (PMTCT) of Human Immunodeficiency Virus (HIV) starting from HIV testing of pregnant women, initiating antiretroviral therapy (ART) or antiretroviral prophylaxis to HIV-positive pregnant women to providing HIV prophylaxis to newborn babies. Gaps in each step can significantly affect the effectiveness of PMTCT interventions. We aimed to determine the gap in initiation of ART/antiretroviral prophylaxis for pregnant women living with HIV, delay in initiation of ART/antiretroviral prophylaxis and factors associated with the delay. Methods This is a cross sectional study using routinely collected programme data from five health facilities providing PMTCT services located at Township Health Departments (THD) of Mandalay, Myanmar. Results There were 363 pregnant women living with HIV enrolled between January 2012 and December 2017. Sixty (16%) women were excluded from the study due to missing data on dates of HIV diagnosis. Of 303 (84%) women included in the study, 89/303 (29%) and 214/303 (71%) were diagnosed with HIV before and during current pregnancy respectively. Among 214 women, 180 (84%) women were started on ART by the censor date (31st March 2018). Among those who started ART, 109 (61%) women had a delay of starting ART > 2 weeks from diagnosis. Women residing in township 4 had a significantly higher risk of delay in initiation of ART/antiretroviral prophylaxis compared to women residing in township 1 [adjusted prevalence ratio 4.2 (95% confidence interval 1.2-14.8]. Conclusions We found that one in four women living with HIV knew their HIV status before current pregnancy. Although the rate of ART/antiretroviral prophylaxis initiation was high among pregnant women living with HIV, there was a delay. Early initiation of ART/antiretroviral prophylaxis among newly HIV diagnosed pregnant women needs to be strengthened.